Cloning and Expression of HA1 Gene of H1N1 Influenza Virus 2009 Pandemic (H1n1pdm09) Indonesia Strain in the Pichia Pastoris Expression System for the Development of Influenza Vaccine - ASRI SULFIANTI; ANDI YASMON; BUDIMAN BELA; FERA IBIRAHIM (Indonesian Society for microbiology, 2015)
Among influenza viral proteins, hemagglutinin 1 (HA1) is the target for neutralizing antibodies which inhibit virus binding to receptor of target cells. This protein is widely developed as subunit recombinant vaccine. In this research, we expressed HA1 protein recombinant from DKI271/2011 Indonesian strain in Pichia pastoris. The identity of this protein was confirmed by western blotting using anti-His T ag and mouse specific antibody HAÂ H1N1pdm09. The use of yeast P . pastoris as an alternative strategy to solve the problems which commonly found in influenza vaccine productions. Expression protein in E. coli has been known to have many problems, while mammalian and insect cells requires special skills and relatively high cost. The analysis of HA1 gene sequences showed no mutation in epitope region which recognized by T dan B cells. Further, this recombinant protein can be used as vaccine candidate in influenza vaccine development.Keywords: Hemagglutinin; Pichia pastoris; vaccine; Influenza Virus; H1N1pdm09.